2015
DOI: 10.7232/jkiie.2015.41.1.105
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Influencing Factors through the Follow-up on Commercialization of Transferred Technology from Government Funded Research Lab : A Case Study of A-institute

Abstract: An empirical analysis study applied to evaluate the effect of critical factors for technology transfer. The research aims to suggest ways of political support in order to facilitate technological transfer and commercialization of public research institute'technology. Based on previous researches, it is determined that five critical factors which effect on technology commercialization. These critical factors are used to derive the order of priority, attribute of the success, and failure factors. The result of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Government support R&D projects, funding support, related laws and institutions -Commercialization environment technology financing, industrial characteristics, market size, market volatility, competitive situation, etc. [30,32] Cooperation partnership collaborative relationships, communications, trust, etc. [19,21,22,31,32] Min and Kim [28] and Min et al [32] have investigated the impact of technologies transferred from PRIs on commercialization success.…”
Section: Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Government support R&D projects, funding support, related laws and institutions -Commercialization environment technology financing, industrial characteristics, market size, market volatility, competitive situation, etc. [30,32] Cooperation partnership collaborative relationships, communications, trust, etc. [19,21,22,31,32] Min and Kim [28] and Min et al [32] have investigated the impact of technologies transferred from PRIs on commercialization success.…”
Section: Environmentmentioning
confidence: 99%
“…The author has concluded that the strategy of engaging the inventor can favorably influence the success of entrepreneurial commercialization. Jung et al [21] and Yun et al [30] have analyzed commercialization success and/or failure factors in technology transfers from GRIs. They found that a company's marketing capability, a developer's cooperation, a CEO's willingness, the market size, and technology originality were major success factors.…”
Section: Environmentmentioning
confidence: 99%
See 3 more Smart Citations